2023
DOI: 10.3389/fpsyg.2023.1071487
|View full text |Cite
|
Sign up to set email alerts
|

The development of visual aesthetic sensitivity in students in China

Abstract: To examine the development of visual aesthetic sensitivity in students in China, 2,387 students from age 9 to age 22 (excluding ages 16–17) were tested by the Visual aesthetic Sensitivity Test-Revised. The development of visual aesthetic sensitivity across ages and genders, and the effect of artistic training on students’ visual aesthetic sensitivity were examined. The data of primary school and junior middle school students were collected by paper tests completed collectively in class, while the data of unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Although we do not have much research on the differences in terms of aesthetics and beauty due to gender and age, there is some evidence that both variables could act as potential confounders. For example, Zhang et al 46 observed that visual aesthetic sensitivity increases with age and is significantly higher in girls than in boys. Similarly, spirituality in older persons [47][48][49] and women 50 tends to increase.…”
Section: Statistic Analysesmentioning
confidence: 99%
“…Although we do not have much research on the differences in terms of aesthetics and beauty due to gender and age, there is some evidence that both variables could act as potential confounders. For example, Zhang et al 46 observed that visual aesthetic sensitivity increases with age and is significantly higher in girls than in boys. Similarly, spirituality in older persons [47][48][49] and women 50 tends to increase.…”
Section: Statistic Analysesmentioning
confidence: 99%